2014
DOI: 10.1042/bj20130847
|View full text |Cite
|
Sign up to set email alerts
|

Differential functions of calpain 1 during epithelial cell death and adipocyte differentiation in mammary gland involution

Abstract: Calpains become activated in the mammary gland early during weaning, cleaving several proteins located mainly in the cell membrane, but also in other organelles such as lysosomes, mitochondria and nuclei. By immunofluorescence and Western blot analysis, we have demonstrated the nuclear translocation of calpain-1 and calpain-2, together with the cleavage of several cytoplasmic nucleoporins in epithelial cells of the lobulo-alveolar compartment. In vivo and in vitro calpain inhibition prevented this nucleoporin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 44 publications
5
11
0
Order By: Relevance
“…Moreover, calpain activation has been identified to be involved in diseases of remodeling (i.e., fibrosis) via mechanisms that remain unclear (54). Interestingly, the predicted substrates for calpain activation not only included key ECM proteins [e.g., collagens and fibrin(ogens)], but also nuclear proteins, such as histones (Figure 6C), which is in-line with previous findings (55). Few studies have identified calpain activation to play a role in hepatic injury.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, calpain activation has been identified to be involved in diseases of remodeling (i.e., fibrosis) via mechanisms that remain unclear (54). Interestingly, the predicted substrates for calpain activation not only included key ECM proteins [e.g., collagens and fibrin(ogens)], but also nuclear proteins, such as histones (Figure 6C), which is in-line with previous findings (55). Few studies have identified calpain activation to play a role in hepatic injury.…”
Section: Discussionsupporting
confidence: 89%
“…Malfunction of nucleo-cytoplasmic transport caused by Ca 2+ dysregulation has been proposed to occur in degenerative diseases39, and excess Ca 2+ influx reportedly disrupts nucleo-cytoplasmic transport as a result of calpain-dependent degradation of NPC components104041, including nuclear lamins and Nups. Disruption of the NPC enabled redistribution of calpains from the cytoplasm to the nucleus across the nuclear membrane during an acute excitotoxic insult10, but the pathogenic role of NPC disruption and the occurrence of NPC disruption during the slow neuronal death process have not been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Although we do not yet know the molecular steps that link calpainopathy to eosinophilic responses, it is notable that CAPN14 belongs to the classical calpain sub-family that comprises one of the major proteolytic systems that mediate protein cleavage (in addition to the proteasome, lysosome, and caspase systems) 47 . Classical calpains are calcium regulatory proteases and their substrates include structural proteins, signaling molecules, transcription factors 48 , 49 , and inflammatory mediators that are germane for allergic responses, such as STAT-6 (signal transducer and activator of transcription 6) and IL-33 50 , 51 , the latter of which shows some linkage with EoE ( Supplementary Figure 7 , Table 2 ). On the basis of the collective data, we propose a model that links the interplay of allergic sensitization with an EoE-specific, IL-13–inducible esophageal response involving CAPN14 .…”
mentioning
confidence: 99%